Empower Educated Unemployment to Support Learning Process Using Website Development - Debby Cyntia Ganesha Putri; Wahyu Sri Handayani; V.N. Sulistyawan (International Journal of Innovation in Enterprise System, 2018)
There are so many graduated people from university, and it affects the number of unemployment who are educated and have specific knowledge in some field. In the other side, in our new education curriculum, students have to learn much by their self. The teacher only needs to monitor them. They do not teach at all. Students usually search the review their courses from the internet which are not valid at all because it is usually opinion from the author. Therefore, the educated person is essential to support education in informal learning. In this paper, authors made an innovation of website which can be used to confront educated unemployment with students to share and learn a specific knowledge. By using a website (such as a common website for marketplace), both of unemployment and student can get the benefit, such as knowledge and skill for students, and also profit/income for unemployment. This informal learning process would be held either online or offline, which unemployment as a teacher and students meet to do learning process. This website would provide benefits for all entities which involved in business processes, such as salary from the student for the teacher and profit from sharing with the teacher, promotion on the website, and sponsor of the website for the service provider. Keywords—Education, students, unemployment, website.